225 The Management of Acute Cholecystitis in a District General setting: An Audit of Practice. (12th October 2021) - Robinson, P; Jones, S; Metcalf, A; Bond, A
Abstract: Aim: The benefits of laparoscopic cholecystectomy during index admission with acute cholecystitis (AC) are multiple. As such, current NICE guidelines dictate that adults with AC undergo laparoscopic cholecystectomy within 1 week of diagnosis. However, significant variation exists with regards to the management of such patients. Here we present the results of an audit of practice at a UK district general hospital and suggest that this standard can be achieved regardless of hospital. Method: Electronic database search at Salisbury District Hospital over a period of 12 months to identify all patients with a coded diagnosis of AC. Electronic Discharge System (EDS) was consulted to assess whether patients underwent laparoscopic cholecystectomy within 7 days of diagnosis. Notes were reviewed for all patients who failed to meet this target to ascertain reasons why. Results: Of the 336 patients coded as AC 8 were excluded due to incorrect coding leaving 328. 285 patients (87%) underwent laparoscopic cholecystectomy within 7 days. Of the 43 that did not, 31 (65%) had clinically justified reasons for delay. 285/297 (96%) patients met the NICE standard. Conclusions: At Salisbury District Hospital 87% patients presenting with AC underwent laparoscopic cholecystectomy within 7 days. Common reasons for failure included: Awaiting further investigation (i.e., ERCP / MRCP), unfit for operative management, patient choice. Excluding justifiable reasons 96% of patients met NICE standards. Poor documentation was the most common cause for failure. Subsequent education and re-audit showed significant improvement. This audit exemplifies that NICE standards for the management of AC can be achieved in a district general setting.